2017
DOI: 10.1007/s10340-017-0863-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal parasitism and host specificity of Trissolcus japonicus in northern China

Abstract: The brown marmorated stink bug, Halyomorpha halys (Stål), native to China, Japan, and Korea, has emerged as a harmful invasive pest of a variety of crops in North America and Europe. The Asian egg parasitoid Trissolcus japonicus has been identified as the most promising agent for classical biological control of invasive H. halys populations. A 4-year study evaluated the fundamental and ecological host ranges of T. japonicus as well as its phenology and impact on H. halys populations in fruit orchards in its na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
145
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 36 publications
(38 reference statements)
13
145
3
Order By: Relevance
“…This gap could be filled by introducing Trissolcus japonicus (Ashmead) (syn. Trissolcus halyomorphae Yang; (Talamas et al, )) from the pest's native range in Asia, which has been identified as most promising for classical biological control of invasive H. halys populations, causing high levels of parasitism in China (Zhang et al, ). The role of predators in reducing H. halys populations in Italy requires further investigations as ongoing laboratory studies indicate that some species can efficiently predate on nymphs, whereas almost no egg consumption occurs (Maistrello et al, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gap could be filled by introducing Trissolcus japonicus (Ashmead) (syn. Trissolcus halyomorphae Yang; (Talamas et al, )) from the pest's native range in Asia, which has been identified as most promising for classical biological control of invasive H. halys populations, causing high levels of parasitism in China (Zhang et al, ). The role of predators in reducing H. halys populations in Italy requires further investigations as ongoing laboratory studies indicate that some species can efficiently predate on nymphs, whereas almost no egg consumption occurs (Maistrello et al, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The natural enemies complex and their impact on H. halys in its native range (Yang, Yao, Qiu, & Li, ; Zhang et al, ) and invaded areas (reviewed in Abram et al, ) was investigated in several earlier studies to evaluate the potential for biological control. In newly invaded areas, the natural enemy community of the alien invasive species is usually absent, but native natural enemies may accept it as food source (predators) or host for reproduction (parasitoids).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its native range, H. halys is attacked by a complex of scelionid and eupelmid egg parasitoids, with Trissolcus japonicus Ashmead (Hymenoptera: Scelionidae) as the most prevalent species (Yang et al, 2009;Zhang et al, 2017). In Europe, native scelionid species typically associated with other pentatomids attempt to attack H. halys eggs, but are unable to complete development (Haye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This parasitoid is known to attack several other species and genera of Pentatomidae (Zhang et al. ), raising further potential for indirect effects to occur between native and invasive North American pentatomids. Recent calls for simultaneous consideration of both benefits and harms in ecological risk assessment of importation biological control programs indicate a need to incorporate both direct and indirect community interactions (Heimpel and Cock ).…”
Section: Introductionmentioning
confidence: 99%